2005
DOI: 10.1038/nsmb1017
|View full text |Cite
|
Sign up to set email alerts
|

The structures of exocyst subunit Exo70p and the Exo84p C-terminal domains reveal a common motif

Abstract: The exocyst is a large complex that is required for tethering vesicles at the final stages of the exocytic pathway in all eukaryotes. Here we present the structures of the Exo70p subunit of this complex and of the C-terminal domains of Exo84p, at 2.0-A and 2.85-A resolution, respectively. Exo70p forms a 160-A-long rod with a novel fold composed of contiguous alpha-helical bundles. The Exo84p C terminus also forms a long rod (80 A), which unexpectedly has the same fold as the Exo70p N terminus. Our structural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
203
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(213 citation statements)
references
References 34 publications
8
203
0
2
Order By: Relevance
“…We found that mutations on exo70-1 did not affect its interaction with Sec8 in the cell (Supplementary Figure 1B). This result is consistent with the previous reports in mammalian and yeast cells that the interaction of Exo70 with the other exocyst components for complex assembly is mediated by the N-terminal domains of Exo70 (Inoue et al, 2003;Dong et al, 2005). …”
supporting
confidence: 93%
See 3 more Smart Citations
“…We found that mutations on exo70-1 did not affect its interaction with Sec8 in the cell (Supplementary Figure 1B). This result is consistent with the previous reports in mammalian and yeast cells that the interaction of Exo70 with the other exocyst components for complex assembly is mediated by the N-terminal domains of Exo70 (Inoue et al, 2003;Dong et al, 2005). …”
supporting
confidence: 93%
“…Moreover, the structural analysis of Exo70 provided important insights into the potential mechanism of membrane association of Exo70 (Dong et al, 2005;Hamburger et al, 2006). On the basis of the crystal structure information of yeast Exo70, we have made mutations on the rat Exo70 residues K632 and K635 (exo70-1), which are positively charged amino acids well conserved in the yeast Exo70 sequence.…”
Section: Pi(45)p 2 Mediates Exocyst Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…Subunits of the COG, exocyst, Dsl1p, and Golgiassociated retrograde protein (GARP) complexes share limited sequence homology (7,13) that has been suggested to reflect convergent evolution (13). Structures, most of them partial, have been reported for one COG complex subunit, two Dsl1p complex subunits, and four exocyst subunits (14)(15)(16)(17)(18)(19)(20); these structures contain one (Cog2p), two (Dsl1p, Sec15, Exo84p), three (Sec6p), four (Exo70p), or five (Tip20p) helix bundle domains. In each of the exocyst and Dsl1p complex structures, the tandem helical domains form an extended, rod-like array (20,21).…”
mentioning
confidence: 99%